Trials and fibrillations : the social context of the coronary experience : a thesis submitted in partial fulfillment [sic.] of the degree of Master of Arts in the Dept. of Sociology at Massey University - Sanders, Jackie (Massey University, 1984)
This thesis has two aims. It is intended that it will provide a detailed description of the experience of a heart attack from the perspective of those who have this illness. It is also intended that it will elaborate a model for undertaking inductive research and theory generation. This model takes as its point of departure the work of Glaser and Strauss (l967). It builds upon their works by attempting to develop a model that will allow for the generation of higher-order sociological concepts from the data gathered in the field. The method developed here has been labelled the "theoretical interpretation" of the research findings. It involves the application of other sociological concepts to the descriptive account of the data. In so doing, it is intended that the low-level descriptive concepts derived from the field-work will be integrated into the more general body of sociological theory. The sociological concepts which are applied to the research findings are the ideological perspective, and the notion of the alienation of self and body.
Keywords: Rehabilitation; Cardiovascular system; Myocardial infarction; Diseases -- Patients